An exploratory study of the patient experience of pharmacist supplementary prescribing in a secondary care mental health setting - Deslandes RE; John DN; Deslandes PN (Centro de Investigaciones y Publicaciones Farmaceuticas, 2015)
Background: Management of chronic disease has become an increasing challenge to the National Health Service in the United Kingdom. The introduction of supplementary prescribing was seen as a possible mechanism to address the needs of this patient group. Individuals with mental illness were considered particularly suitable for management in this way. Objective: To explore the views and experiences of patients with mental illness on being managed by a pharmacist supplementary prescriber in a secondary care outpatient setting. Methods: A study of patient experiences utilising semi-structured interviews and self-completion diaries was adopted. Eleven patients participated in the study. Data were analysed utilising code and retrieve, and content analysis respectively. Results: Patients valued the increased accessibility to, and continuity of, their prescriber compared with their experience of other healthcare professionals. Patients reported they were able to trust the pharmacist's knowledge of medication, were provided with sufficient information regarding reasons for treatment and side effects, and felt that they had an active role in decisions concerning their healthcare. Conclusions: This exploratory study showed that patients had positive views of being managed by a supplementary prescriber. However, it should be noted that the number of participants was small. It is therefore important that further, more wide ranging research is conducted to evaluate pharmacist prescribing within mental health settings.